2013
DOI: 10.1007/s12011-013-9819-0
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Trioxide Co-exposure Potentiates Benzo(a)pyrene Genotoxicity by Enhancing the Oxidative Stress in Human Lung Adenocarcinoma Cell

Abstract: Although both arsenic trioxide (As2O3) and benzo(a)pyrene (BaP) are well-established human carcinogens, the interaction between As2O3 and BaP is synergistic or antagonistic remains controversial in terms of the existing studies. In addition, the mechanisms responsible for the combined effects are still unclear. In this study, we examined the potential interactive effects between As2O3 (1, 5, and 10 μM) and BaP (5, 10, and 20 μM) in cultured A549 cells by treating with BaP and As2O3 alone or in combination at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…2 and 3). This is supported by previous findings showing that As 2 O 3 -induced ROS can result in DNA strand breaks and chromosome breakage [Miller et al, 2002;Hei and Filipic, 2004;Selvaraj et al, 2012;Chen et al, 2013b]. We demonstrated that As 2 O 3 genotoxicity was effectively suppressed by 5 lM resveratrol (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…2 and 3). This is supported by previous findings showing that As 2 O 3 -induced ROS can result in DNA strand breaks and chromosome breakage [Miller et al, 2002;Hei and Filipic, 2004;Selvaraj et al, 2012;Chen et al, 2013b]. We demonstrated that As 2 O 3 genotoxicity was effectively suppressed by 5 lM resveratrol (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…It was observed that colon epithelial cells treated with BaP had lower SOD activity and GSH levels as compared to the untreated controls (see Figure 2). Our results are supported by previous reports [23,26], which have shown that GSH and SOD are overutilized during the increased demand for detoxification of free radicals caused by the presence of BaP [24]. Moreover, BaP not only affected protein expression of the colon epithelial cells to a relatively high extent but also damaged their DNA and mRNA [26].…”
Section: Discussionsupporting
confidence: 91%
“…To evaluate the potential of the inactivated bifidobacterial strain in relieving BaP damage, 50 µM BaP was selected as an inhibition concentration for the following tests. Partially, oxidative stress has been regarded to be responsible for the cytotoxicity following BaP exposure, as BaP causes cellular oxidative damage by increasing the levels of free radicals in the cells [23,24]. The intracellular redox status is tightly regulated by the presence of enzymatic and non-enzymatic antioxidants, which play important roles in maintaining the free radical balance in the organisms [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many examples of interaction among multiple exposures exist in the literature on co-exposures and resulting biological responses. Arsenic (As) was found to potentiate the genotoxicity of benzo [a]pyrene by inducing DNA adducts in Hep-1 mouse hepatoma cells (Maier et al 2002), and by enhancing oxidative stress in human lung adenocarcinoma cells (Chen et al 2013). Interaction can occur between ultraviolet radiation and heavy metals as measured by DNA damage in human keratinocytes and in SKH-1 hairless mice (Cooper et al 2013).…”
Section: Immortalizationmentioning
confidence: 99%